2012
DOI: 10.5194/os-8-959-2012
|View full text |Cite
|
Sign up to set email alerts
|

Arctic surface temperatures from Metop AVHRR compared to in situ ocean and land data

Abstract: Abstract. The ice surface temperature (IST) is an important boundary condition for both atmospheric and ocean and sea ice models and for coupled systems. An operational ice surface temperature product using satellite Metop AVHRR infra-red data was developed for MyOcean. The IST can be mapped in clear sky regions using a split window algorithm specially tuned for sea ice. Clear sky conditions prevail during spring in the Arctic, while persistent cloud cover limits data coverage during summer. The cloud covered … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…T 2 m could have been utilized here. This type of measurement has been used in other studies, such as Hall et al (2004) and Dybkjaer et al (2012), to validate satellite observations as, although measured at a different height to satellite T s , these temperatures are highly correlated (Comiso, 2003). But comparing different types of temperature is not ideal, in particular when the relationship between them can be complex (Adolph et al, 2018;Good et al, 2017;Vihma & Pirazzini, 2005).…”
Section: 1029/2019jd030262mentioning
confidence: 99%
“…T 2 m could have been utilized here. This type of measurement has been used in other studies, such as Hall et al (2004) and Dybkjaer et al (2012), to validate satellite observations as, although measured at a different height to satellite T s , these temperatures are highly correlated (Comiso, 2003). But comparing different types of temperature is not ideal, in particular when the relationship between them can be complex (Adolph et al, 2018;Good et al, 2017;Vihma & Pirazzini, 2005).…”
Section: 1029/2019jd030262mentioning
confidence: 99%
“…The determination of high latitude surface temperatures is an important factor in assessing climate change in polar environments [1][2][3][4][5][6]. This is particularly true in the Arctic where surface air temperatures are increasing more rapidly than the global average [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, as Hori et al (2006) demonstrated by in situ observations, snow emissivity varies depending on wavelength, snow type and exitance angle. Thus, the dependence of snow emissivity on snow type and exitance angle has to be taken into account in an analysis of the Earthʼs radiative balances over the polar region (Dybkjaer et al, 2012). Snow emissivity is also an indispensable boundary condition for estimating the thermal emissive properties of the ground surface for polar-night cloud detection (Yamanouchi et al, 1987;Kadosaki et al, 2002).…”
Section: Introductionmentioning
confidence: 99%